2013
DOI: 10.1002/anie.201304497
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Tandem Cycloisomerization/Cope Rearrangement: An Efficient Access to the Hydroazulenic Motif

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Trienyne 382 cyclizes following a 5- endo -dig pathway through cyclopropyl gold(I) carbene 383 , which gives 384 by 1,2-acyloxy migration followed by a Cope rearrangement to afford hydrozulenic derivative 385 (Scheme 121 ). 325 …”
Section: Gold(i)-catalyzed Reactions Of Propargylic Carboxylatesmentioning
confidence: 99%
“…Trienyne 382 cyclizes following a 5- endo -dig pathway through cyclopropyl gold(I) carbene 383 , which gives 384 by 1,2-acyloxy migration followed by a Cope rearrangement to afford hydrozulenic derivative 385 (Scheme 121 ). 325 …”
Section: Gold(i)-catalyzed Reactions Of Propargylic Carboxylatesmentioning
confidence: 99%
“…Accordingly, these substrates undergoes an efficient and highly selective reorganization reaction by avoiding competitive 1,3-ester shift or Nazarov-type cyclization. [137] However, Nazarov cyclization is possible in enynyl acetates via tandem Au(I)-catalyzed [3,3]-rearrangement trigger (via 1,3acetyl shift) to lend 2-substituted cyclopentenones. [138] Fensterbank's team in one of their recent works have shown that the 5,7,3-tricyclic skeleton of neomerane sesquiterpenes 41 can be easily synthesized from enynyl propargylic esters 42 featuring Au(I)-catalyzed selective 1,2-acyloxy migration/intramolecular cyclopropanation sequence.…”
Section: 2-selective Ester Shift Reactionsmentioning
confidence: 99%
“…It was shown by the Gagosz's group that hydroazulenic frameworks 39 can be synthesized via Au(I)‐catalyzed cascade 1,2‐ester shift/cycloisomerization/Cope rearrangement of linear trienynes 40 (Scheme 11, eq 1). Accordingly, these substrates undergoes an efficient and highly selective reorganization reaction by avoiding competitive 1,3‐ester shift or Nazarov‐type cyclization [137] . However, Nazarov cyclization is possible in enynyl acetates via tandem Au(I)‐catalyzed [3,3]‐rearrangement trigger ( via 1,3‐acetyl shift) to lend 2‐substituted cyclopentenones [138] .…”
Section: Propargyl Ester Rearrangementsmentioning
confidence: 99%
“…Gagosz proposed a similar 1,2-OAc shift followed by the cyclopropanation/Cope rearrangement to afford the desired fused cycloheptadiene derivatives (Scheme 3.14d). 52 Yu has shown that it is possible to use dienediynes 3.15a in these types of cyclization reactions. He proposed that the mechanism goes through the cyclopropanation/…”
Section: Scheme 312 Au-catalyzed Formal (4+3)-cycloadditions Of Diazmentioning
confidence: 99%